(untitled) (Contemporary Education and Teaching Research, 2025)
Rural revitalization is the core mandate of the “Bai-Qian-Wan” Project and supporting this revitalization constitutes both a statutory duty and a policy imperative for vocational colleges and universities. At present, vocational education’s capacity to empower rural revitalization is impeded by multiple dilemmas: insufficient coordination among stakeholders, the contraction of agriculture-related programs, an imbalanced allocation of resources, and a mismatch between skills training and local needs. Drawing on an analysis of the underlying empowerment mechanisms and situated within the strategic framework of Guangdong Province’s “Bai-Qian-Wan” Project this study proposes a multi-actor collaborative governance model—integrating government, vocational institutions, enterprises, and township-village actors—guided by collaborative governance theory. Through program optimization, talent deployment to rural areas, skills upgrading, and institutional innovation, the model seeks to overcome the structural barriers inhibiting vocational education’s contribution to rural revitalization and to sustain the efficient advancement of the “Bai-Qian-Wan” Project.